(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
The plant Morinda citrifolia L. (noni) has been the focus of many recent studies due to its potential effects on treatment and prevention of several diseases. However, there are few in vivo and in vitro studies concerning its composition and antioxidant capacity. The aim of the present study was to determine the total polyphenol content (TPC) and antioxidant capacity of a juice commercialized as noni juice, but containing grape, blueberry and noni fruits. Commercial noni juice was compared against its separate constituents of blueberry and grape juice. Folin-Ciocalteu and DPPH methods were used to determine the concentration of total polyphenol content and antioxidant activity, respectively. Commercial noni juice presented higher values of TPC (91.90 mg of gallic acid/100 mL juice) and antioxidant activity (5.85 mmol/L) compared to its 5% diluted constituents. Concentrated blueberry juice presented higher TPC and antioxidant activity than the other juices analyzed. Considering that the blueberry and grape juices account for only 10% in the composition of commercial noni juice, it can be inferred that these two components contribute significantly to the antioxidant activity. Therefore, additional studies are necessary in order to elucidate the contribution of the noni juice as an antioxidant.